PENINGKATAN AKTIVITAS BELAJAR MATEMATIKA MELALUI PENDEKATAN PROBLEM BASED LEARNING BAGI SISWA KELAS 4 SD - Rahmadani, Normala; Anugraheni, Indri (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2017)
ABSTRACTThe purpose of this study is to determine whether the increase in learning activities mathematics can be pursued through the approach of PBL grade 4 students SDN Petirrejo 2nd semester of 2017. Data collection techniques using observation techniques, with research instruments in the form of observation sheet of learning activities Mathematics. Technique of data analysis of this research using comparative descriptive statistical technique that is technique of analysis to compare number of students who have high learning activity of Mathematics between cycle I and cycle II. The results showed that, the increase in learning activity of Mathematics can be done through the approach of PBL grade 4 students. Cycle I to cycle II has increased. From visual activity from cycle I the percentage 95,8% to cycle II that is 100% increase of the cycles of cycle I to cycle II is 4,2%. At the oral activity of cycle I the percentage of 37,5% to cycle II 79,16% increase the cycles percentage to cycle II equal to 41,6%. At the activity of listening cycle I is 62,5% to cycle II 70,83% increase of its percentage from cycle I to cycle II equal to 8,33%. In the activity of writing from cycle I 79.1% to cycle II the percentage of 83.33% had an increase of 12.5%, and in the mental activity percentage of cycle I from 62.5 to cycle II 70.83% increased by 8.33 %.